1997
DOI: 10.1007/s002130050186
|View full text |Cite
|
Sign up to set email alerts
|

The cholecystokinin-B receptor antagonist CI-988 failed to affect CCK-4 induced symptoms in panic disorder patients

Abstract: The effects of the cholecystokinin-B (CCK-B) receptor antagonist CI-988 on symptoms elicited by the cholecystokinin tetrapeptide (CCK4) were studied in DSM-IIIR patients with panic disorder. The study employed a double-blind, two-period incomplete block design. Patients (n = 14) received two different dosages of CI-988 (50 mg or 100 mg) or placebo 2 h prior to an IV bolus injection of CCK4 (20 micrograms) on two separate occasions. The primary efficacy parameter was the total intensity score on the Panic Sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 25 publications
(14 reference statements)
1
10
0
1
Order By: Relevance
“…This is evident in clinical trials of CCK2 antagonists wherein no effect was found following the administration of several CCK2 antagonists in patients with generalized anxiety disorder or panic disorder (Adams et al, 1995;Kramer et al, 1995;van Megen et al, 1997;Pande et al, 1999). Several results from the animal literature also support the notion that CCK2 antagonists are not necessarily anxiolytic when administered alone (Dawson et al, 1995;Johnson and Rodgers, 1996).…”
Section: Discussionmentioning
confidence: 89%
“…This is evident in clinical trials of CCK2 antagonists wherein no effect was found following the administration of several CCK2 antagonists in patients with generalized anxiety disorder or panic disorder (Adams et al, 1995;Kramer et al, 1995;van Megen et al, 1997;Pande et al, 1999). Several results from the animal literature also support the notion that CCK2 antagonists are not necessarily anxiolytic when administered alone (Dawson et al, 1995;Johnson and Rodgers, 1996).…”
Section: Discussionmentioning
confidence: 89%
“…Despite differences in dosage (20-100 μg, 50 μg being used in five studies) stress hormones (ACTH, cortisol or prolactin) increased after CCK-4, regardless of the subject experiencing a PA or not , van Megen et al 1997, Shlik et al 1997, Flint et al 2000, Strohle et al 2000, Zwanzger et al 2001. As an exception, however, van Megen et al (1996) have reported no increase in either prolactin or cortisol in 12 PD patients after administration of 25 e 50 μg of CCK-4, the panic rates being 44% and 71%, respectively.…”
Section: Colecystokinin Agonistsmentioning
confidence: 95%
“…However, L365260 was not able to block the endogenous panic attacks not stimulated by CCK-4 in humans 55 . Furthermore, clinical tests performed with the CCK B receptor antagonist CI988 revealed that this compound was ineffective in patients with generalized anxiety disorder 56 and also failed to reduce CCK-4 induced symptoms in panic disorder patients 57 . It is possible that this lack of effect is related to the limited solubility and brain penetrability of these first generation CCK B antagonists (Box 1).…”
Section: Depression Anxiety and Stress-related Disordersmentioning
confidence: 99%